CO-5: A promising bajra napier hybrid variety for coconut gardens and homesteads - C., Deepthi; Usha C. Thomas (Journal of Tropical Agriculture, 2025)
BBajra napier hybrid is a highly accepted perennial fodder grass among the dairy farmers of Kerala, as it is very well suited for the climatic conditions of Kerala. Per capita land availability of Kerala is very low, making it essential to utilize the available land efficiently. Knowledge on shade tolerance of Bajra Napier grass varieties will help the farmers to select best variety for intercropping in coconut gardens as well as homesteads with different tree species. In this scenario, a study was conducted at College of Agriculture, Vellayani to identify the effect of varying shade levels on the yield and quality of promising varieties of Bajra Napier hybrid. The experiment was laid out in split plot design with 12 treatment combinations replicated three times. Main plot treatments were different shade levels, which included open, 25 per cent shade and 50 per cent shade and subplot treatments were major Bajra Napier hybrid varieties include viz., Suguna, Susthira, CO-3 and CO-5. Shade had remarkable effect on yield and quality of the grass varieties. Green fodder yield and dry fodder yield decreased with increase in shade. Among quality characters, crude protein and oxalate content increased with increase in shade but crude fibre content decreased with increase in shade. CO-5 recorded maximum green fodder yield under open (173.63 t ha-1) and 50 per cent shade level (116.93 t ha-1) as well as dry fodder yield (38.20 t ha-1 and 25.72 t ha-1 respectively under open and 50 % shade level). Variety Suguna under 25 per cent shade recorded maximum green fodder (101.85 t ha-1) and dry fodder yield (19.99 t ha-1). Considering yield and quality of different BN hybrid varieties under varying shade levels, it can be inferred that CO-5 thrives optimally when cultivated in open areas and 50 per cent shade, while Suguna performs best in fields with 25 per cent shade.